Jasmonates modulate sphingolipid metabolism and accelerate cell death in the ceramide kinase mutant acd5. Issue 3 (7th August 2021) - Huang, Li-Qun; Chen, Ding-Kang; Li, Ping-Ping; Bao, He-Nan; Liu, Hao-Zhuo; Yin, Jian; Zeng, Hong-Yun; Yang, Yu-Bing; Li, Yong-Kang; Xiao, Shi; Yao, Nan
Abstract : Methyl-jasmonate-mediated acceleration of the acd5 cell death phenotype and modulation of sphingolipid metabolism require an intact jasmonate pathway. Abstract: Sphingolipids are structural components of the lipid bilayer that acts as signaling molecules in many cellular processes, including cell death. Ceramides, key intermediates in sphingolipid metabolism, are phosphorylated by the ceramide kinase ACCELERATED CELL DEATH5 (ACD5). The loss of ACD5 function leads to ceramide accumulation and spontaneous cell death. Here, we report that the jasmonate (JA) pathway is activated in the Arabidopsis ( Arabidopsis thaliana ) acd5 mutant and that methyl JA treatment accelerates ceramide accumulation and cell death in acd5 . Moreover, the double mutants of acd5 with jasmonate resistant1-1 and coronatine insensitive1-2 exhibited delayed cell death, suggesting that the JA pathway is involved in acd5 -mediated cell death. Quantitative sphingolipid profiling of plants treated with methyl JA indicated that JAs influence sphingolipid metabolism by increasing the levels of ceramides and hydroxyceramides, but this pathway is dramatically attenuated by mutations affecting JA pathway proteins. Furthermore, we showed that JAs regulate the expression of genes encoding enzymes in ceramide metabolism. Together, our findings show that JAs accelerate cell death in acd5 mutants, possibly by modulating sphingolipid metabolism and increasing ceramide levels.